Differences of Local Students and Non-Local Students Independence - Rahmawati, Putri; Martunis; Jamilah Aini Nasution (Universitas Lancang Kuning, 2023)
Independent students are inherently capable of self-management, not relying on emotional support from others, especially parents, able to make independent decisions, and possess a strong set of principles. Furthermore, the objectives of this research are as follows: 1) to determine the level of independence among local students at FKIP USK, 2) to determine the level of independence among non-local students at FKIP USK, 3) to identify the differences in independence between local and non- local students at FKIP USK. This research employs a quantitative approach with a comparative research design. The population of this study consists of active S1 FKIP USK students from the 2022 cohort, who come from outside the Aceh province and do not live with family members or relatives (for local students), as well as those who reside in and originate from Banda Aceh or live with their parents (for non-local students), totaling 425 students. The research sample comprises 133 FKIP USK students, with 60 local students and 73 non-local students, selected using a simple random sampling technique. Based on the research findings, it was known that the level of independence among local students predominantly falls into the high category (60%), while independence among non-local students predominantly falls into the moderate category (49%). The research results show an Asymp. Sig. (2-tailed) value of 0.026 ˂ 0.05, indicating that there was a difference in independence between local and non- local students at FKIP USK, as evidenced by the detailed mean rank values, with local students (75.18) having a higher mean rank than non-local students (60.27). Therefore, it can be concluded that the hypothesis in this research is accepted.